Ответ:
Пошаговое объяснение:
25) (х-16)*9=126
х-16= 126:9
х-6= 14
х= 20
26) 28(х+5)= 224
х+5= 224 :8
х+5= 28
х= 23
27) (х+76) : 7= 15
х+76= 15*7
х+76= 105
х= 105 -76
х= 29
28) 2х+29=97
2х= 97-29
2х= 68
х= 68 : 2
х= 34
29) х:5=15
х= 15*5
х=75
30) (х-5):3= 5
х-5 = 5*3
х-5= 15
х= 15+5
31) (24-х)+37=49
(24-х)= 49-37
24-х= 12
-х= 12-24
х= 12
32) (18+х) : 2= 10
18+х= 10 *2
18+х= 20
х= 20-18
х=2
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
25) (х-16)*9=126
х-16= 126:9
х-6= 14
х= 20
26) 28(х+5)= 224
х+5= 224 :8
х+5= 28
х= 23
27) (х+76) : 7= 15
х+76= 15*7
х+76= 105
х= 105 -76
х= 29
28) 2х+29=97
2х= 97-29
2х= 68
х= 68 : 2
х= 34
29) х:5=15
х= 15*5
х=75
30) (х-5):3= 5
х-5 = 5*3
х-5= 15
х= 15+5
х= 20
31) (24-х)+37=49
(24-х)= 49-37
24-х= 12
-х= 12-24
х= 12
32) (18+х) : 2= 10
18+х= 10 *2
18+х= 20
х= 20-18
х=2